The Effect of Commercial Toothpaste Containing Aloe Vera on Dental Plaque and Gingivitis: A Double-Blind Randomized Clinical Trial - Ousama Aziz Ibrahim; Ahmed Ali Mohsin; Mohammad Hasan Alhammashi; Jafar Sadik Jafa (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: Aloe vera is a medical plant which has the greater medicinal value and enormous properties forcuring and preventing gingivitis and oral diseases. This study aims to evaluate the effect of a commercialtoothpaste containing Aloe vera on the reduction of plaque and gingivitis.Material and methods: 24 patients diagnosed with generalized gingivitis, randomly divided into 2 groups,patients in the test group (n=12) used toothpaste containing Aloe vera, and patients in the control group(n=12) used toothpaste containing fluoride. Plaque Index (PI), Gingival Index (GI), and Bleeding on Probing(BOP) were assessed at days 0 and 30. Subjects were asked to brush their teeth with the stated toothpaste, twicea day, for 30 days. the data on toothpaste tubes were masked for both patients and examiner.Results: All clinical parameters showed a significant reduction on 30th day in both test and control groups,but no significant differences between groups.Conclusion: The results of the present study indicate that commercial toothpaste containing Aloe vera did notshow an additional effect on plaque and gingivitis compared to the control fluoridated toothpaste.